The Impact of On-Campus Health Promotion Activities on Healthy Lifestyle Behaviours of Indian University Students - Manisha Gore; Dr Rajiv Yeravdekar; Dr. Kavitha Menon (ACHSM, 2023)
Background: A paucity of information exists on the impact of health-promoting activities conducted in low-and-middle-income country settings including Indian Higher Education Institution (HEI). Health promoting universities offer a variety of on-campus health promotion activities to improve the health and lifestyle of the university students. However, the information on the impact of such programmes are scanty. Aim: The study aimed to assess the university students' Health-Promoting Lifestyle Profiles (HPLP) before and after exposure to the ongoing on-campus health promotional activities for one year. Methods: All freshmen admitted to an international university in India, with campuses across the major cities, were enrolled in the study. The study was conducted in two phases; phase 1 assessed the baseline existing HPLP scores of these students and phase 2 investigated the impact of on-campus health promotion activities for one year on the HPLP scores, a proxy for healthy lifestyle behaviour. Results: The total HPLP scores differed significantly between the two phases (137.9 vs 130.9; p=0.000). Similarly, a significant increase in physical activity scores between the two phases was observed (17.8 vs 19.5; p=0.000). A gender-wise comparison of total and sub-scale HPLP scores of phase I reported significantly higher total HPLP, health responsibility, nutrition, and interpersonal sub-scale scores in females; and significantly higher physical activity scores in males (18.5 vs 17.3; p=0.000). In phase 2, females had significantly higher scores in total HPLP, nutrition, interpersonal, and physical activity sub-scale scores. In both phases females had significantly higher total HPLP scores than males (Phase 1: 137.6 vs 139.8; p=0.000; Phase 2 130.6 vs 131.3; p=0.000). Conclusions: A gender-wise difference on the impact of on-campus health promoting activities with higher impact on females was observed. A more focused, systematic and targeted approach through curricular, co-curricular and extracurricular courses may further improve the HPLP scores of Indian university students.